Dynamics of invasive mosquitoes: introduction pathways, limiting factors, and their potential role in vector-borne pathogen transmission - Yan, Jiayue; Mackay, Andrew J.; Stone, Chris M. (Frontiers in Tropical Diseases, 2024)
The blooming of global trade and travel and the intensification of global changes over the past decades are thought to be important drivers of accelerated range expansions of vector-borne pathogens (VBPs), with the potential to cause severe disease outbreaks around the world. As a bridge between hosts and pathogens, mosquitoes play a central role in the transmission of VBPs. With modern oversea/air transportation facilitating the introduction of different mosquito species into novel regions, there is concern that this may escalate the introduction and subsequent spread of introduced VBPs in those regions. Despite these potential impacts, there is still a lack of comprehensive understanding of the ecology of invasive mosquitoes and the consequences they have for VBP introductions and transmission intensity. Here we review common introduction pathways, limiting factors for the establishment and spread of invasive mosquito species and explore their role in the transmission of VBPs in invaded regions. We also highlight the major challenges in invasive mosquito surveillance and control and identify key research questions for advancing future control strategies and practices. This body of knowledge may contribute to the prevention of mosquito introductions, as well as risk assessment and risk management of VBPs.